2008
DOI: 10.1007/s10021-008-9205-5
|View full text |Cite
|
Sign up to set email alerts
|

High Foliar and Soil Nitrogen Concentrations in Central Appalachian Forests

Abstract: Regional topography and climate variation yield differences in ecosystem attributes that make spatially scaled estimates of forest productivity challenging. Foliar nitrogen is a primary indicator of forest ecosystem productivity and is used in regional estimates of terrestrial productivity, but this characteristic has not been well described in the Central Appalachian region. Here we describe foliar and soil N variation among species and elevations at two spatial scales in the Central Appalachian region: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…spectrum (Wright et al , 2005a. The positive correlation of foliar N with regional-scale N deposition corroborates evidence of foliar N enrichment reported in numerous studies in northeastern forests (McNeil et al 2007, 2012, Davis et al 2009, Crowley et al 2012). Correlations of foliar d 15 N concentrations with mean annual temperature (positive) and precipitation (negative) agree with results in Amundson et al (2003), Craine et al (2009), andSerbin et al (2014).…”
Section: Discussionsupporting
confidence: 88%
“…spectrum (Wright et al , 2005a. The positive correlation of foliar N with regional-scale N deposition corroborates evidence of foliar N enrichment reported in numerous studies in northeastern forests (McNeil et al 2007, 2012, Davis et al 2009, Crowley et al 2012). Correlations of foliar d 15 N concentrations with mean annual temperature (positive) and precipitation (negative) agree with results in Amundson et al (2003), Craine et al (2009), andSerbin et al (2014).…”
Section: Discussionsupporting
confidence: 88%
“…Schuler (2004) also found that the interval of harvest was important for sustaining annual woody increment growth, but changes in wood production were partially mediated by changes in species composition. In another recent study, we found that the interaction of species and N availability has important implications for the sustainability of forest C stores in mature West Virginia forests (Davis et al, 2009). Here, we estimated C storage at the ecosystem scale, but it should be noted that biased timber species selections would influence the effect of harvests reported here.…”
Section: Predictedmentioning
confidence: 96%